Upaya Mengurangi Intensitas Nyeri Persalinan dengan Teknik Massage Effleurage Menggunakan Minyak Aromaterapi Mawar - Hernawati, Erni; Fitriani, Hanny (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Pain during labor can cause psychological distress. As many as 87% of postpartum blues occur from 2 weeks after delivery to 1 year, 10% with depression, and 3% with psychosis. Giving effleurage massage is one of the non-pharmacological methods. In addition to massage, there is also rose aromatherapy oil containing Nerol, which is usually used as a therapeutic oil and can have a calming effect, reduce depression and stress, relax tension, relax the nerves, and reduce labor pain. The purpose of this study was to analyze the impact of effleurage massage using rose aromatherapy oil on reducing labor pain during active phase I at PMB Cimahi City in 2022. This type of research uses a true experiment with a pretest-posttest design and a control group design, which divides 2 groups of respondents into an intervention group and a control group. The results showed that the average pain intensity of respondents before being given treatment in the intervention group was 7.1, while the average in the control group was 7.0. The average pain intensity after giving effleurage massage using rose aromatherapy oil in the experimental group was 5.05, while the average in the control group was 7.02. There was a significant difference in the average pain intensity in the experimental group before and after being given effleurage massage using rose aromatherapy oil. Thus, the provision of effleurage massage using rose aromatherapy oil is proven to reduce the level of pain in laboring mothers. Keywords: Aromatherapy Oil; Labor Pain; Massage Effleurage.